Population pharmacokinetics of thrombomodulin alfa in pediatric patients with hematological malignancy and disseminated intravascular coagulation. Issue 3 (12th October 2016) - Takeuchi, Masanobu; Tanoshima, Reo; Miyagawa, Naoyuki; Sarashina, Takeo; Kato, Hiromi; Kajiwara, Ryosuke; Ito, Shinya; Goto, Hiroaki
Abstract: Background: Thrombomodulin alfa (TM‐α) is a new class of anticoagulant drug for patients with disseminated intravascular coagulation (DIC). This study aimed to determine the pharmacokinetics of TM‐α and determine the optimal dose in pediatric patients with hematological malignancy and DIC. Procedure: Pediatric patients with hematological malignancy and DIC were administered TM‐α at a dose of 0.06 mg/kg (380 U/kg) over 30 min every 24 hr. Blood samples were taken at steady state before the start, immediately after the end, and 24 hr after the start of the sixth administration. Population pharmacokinetic analysis was performed using sparse samples with the nonlinear mixed‐effect modeling program NONMEM ®, version 7.3. Results: The actual and predicted plasma concentrations of TM‐α based on the final population pharmacokinetic model showed a good linear correlation. Clearance and volume of distribution of TM‐α were affected by body weight. The clearance of TM‐α in pediatric patients with hematological malignancy and DIC was higher than that in adults as previously reported. Six of eight patients did not achieve the target trough concentration at steady state. Furthermore, the pharmacokinetic simulation based on the estimated pharmacokinetic parameters from the final model demonstrated that TM‐α administered at a dose of 0.06 mg/kg every 24 hr also failed to achieve the target trough concentration at steady state in the majority of pediatric patients. Conclusions: Our study shows that further dose adjustment of TM‐α is necessary considering the higher clearance per body weight in pediatric patients with hematological malignancy and DIC.